2020
DOI: 10.1016/j.compscitech.2020.108450
|View full text |Cite
|
Sign up to set email alerts
|

GO-CNTs hybrids reinforced epoxy composites with porous structure as microwave absorbers

Abstract: Foam structures with epoxy as matrix and both carbon nanotubes (CNTs) and their hybrids with graphene oxide (GO-CNTs) as absorber were fabricated, and their microwave absorbing and electromagnetic properties were investigated in the frequency range of 1-18 GHz. The fillers and bubbles were uniformly distributed in the composites. The complex permittivity and electrical conductivity of the composites increased as the fillers' content increasing. The best performance of the reflection loss (RL) can be obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 35 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Different amounts of SiO 2 were deposited on the CMF surface by a typical method [24]: First, CMF was put into a 1L flask with distilled water (100 mL) and ethanol (400 mL). After stirring for 1h, the ammonium hydroxide was added into the dispersion for adjusting the pH to 9.0.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different amounts of SiO 2 were deposited on the CMF surface by a typical method [24]: First, CMF was put into a 1L flask with distilled water (100 mL) and ethanol (400 mL). After stirring for 1h, the ammonium hydroxide was added into the dispersion for adjusting the pH to 9.0.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In our previous work, we have reported the CVD growth of CNT on the surface of graphene pre-deposited by a SiO 2 layer [24]. Thanks to the existence of SiO 2 , the obtained hybrid showed a regular morphology and an enhanced connection between CNT and substrate.…”
Section: Introductionmentioning
confidence: 96%
“…Hybrid polymer nanocomposites are becoming popular due to their unique combination of properties, which are not possible when a single filler system is used. In the past, several researchers demonstrated that the combination of properties could be achieved by combining two or more different types of fillers [1][2][3][4]. The synthesis of a CNT/alumina hybrid compound has been reported in previous works [5][6][7], where its composites demonstrated good mechanical and thermal properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 16 ] prepared polyurethane/GO composite foams by impregnation, and the results showed that the reflection loss of the foam with a density of 0.027 g/cm 3 can reach −46.2 dB as the addition amount of GO was 30%. Liu et al [ 17 ] prepared a hybrid absorbing agent containing GO and CNTs by a one‐step chemical vapor deposition method, which was then used as a absorber of an epoxy‐based foam with AIBN as foaming agent. This foam exhibited a reflection loss value of −40 dB and a broad effective absorption bandwidth (7.1 GHz).…”
Section: Introductionmentioning
confidence: 99%